The use of precious metals in restorative dentistry - Turaigi, Osama Mohammed Al; Sahaly, Laila Mohammed Al; Hamdi, Sabreen Ali; Turkstani, Halah Mohammad Al; Refai, Hind Jumah Al; Naqadi, Sara Hussain (International Journal Of Community Medicine And Public Health, 2024)
This review delves into the historical and contemporary use of precious metals in restorative dentistry, tracing the evolution from ancient practices to modern technological advancements. It underscores the critical role of metallic materials, such as gold, silver, copper, and alloys like cobalt-chromium and titanium, in dental restorations due to their superior mechanical properties, including high elastic modulus, tensile strength, and hardness. These materials are favored for their biocompatibility, corrosion resistance, and adaptability to various manufacturing processes, including casting, mechanical processing, and advanced methods like CAD/CAM, laser sintering, and welding. Despite the advent of alternative materials catering to aesthetic preferences, metals maintain their relevance in dentistry for structural components in prosthetics, demonstrating significant advancements in dental material technology. The review highlights the importance of understanding the properties and behaviors of these materials within the oral cavity to ensure the quality and durability of dental restorations. Through a comprehensive literature search and analysis of metallurgy, manufacturing, and classification, this paper presents a thorough exploration of the indispensable role of precious metals in enhancing dental health and restorative practices.